2019
DOI: 10.1016/j.jsxm.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Shock Wave Therapy in Sexual Medicine—Clinical Recommendations from the European Society of Sexual Medicine (ESSM)

Abstract: Introduction: Low-intensity shockwave therapy (LISWT) has been investigated for the treatment of uroandrological disorders including erectile dysfunction (ED), Peyronie's disease (PD) and chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) with controversial findings. Aim: To review the evidence on LISWT for ED, PD, and CP/CPPS and provide clinical recommendations on behalf of the European Society of Sexual Medicine. Methods: Medline and Embase databases were searched for randomized clinical trials (RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 45 publications
3
55
0
2
Order By: Relevance
“…There was no significant morphologic change in fibromas on ultrasonography, with the exception of reduced thickness, and there was no case in which the fibroma was completely resolved after ESWT. This result is similar to previous reports on penile fibromatosis, in which ESWT is unlikely to reduce the size of the fibroma [14,15,23]. There are only two reports that ESWT reduced size of penile fibroma and improved penile curvature [17,18].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…There was no significant morphologic change in fibromas on ultrasonography, with the exception of reduced thickness, and there was no case in which the fibroma was completely resolved after ESWT. This result is similar to previous reports on penile fibromatosis, in which ESWT is unlikely to reduce the size of the fibroma [14,15,23]. There are only two reports that ESWT reduced size of penile fibroma and improved penile curvature [17,18].…”
Section: Plos Onesupporting
confidence: 90%
“…Extracorporeal shock wave therapy (ESWT) has been used as a safe alternative treatment for chronic refractory musculoskeletal disease, such as plantar fasciitis Achilles tendinopathy and gluteal tendinopathy [10][11][12][13]. Previous studies have shown that ESWT also can be therapeutically applied to various forms of fibromatosis such as penile fibromatosis [14][15][16][17][18][19] and palmar fibromatosis [20][21][22] to reduce pain and soften nodules, although it did not affect the physical size of the nodules [3,15,16,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…Most published studies did not extend beyond 2 years follow-up, and one study that reviewed patients at 4-year follow-up [43] showed that the observed clinical improvement is not sustained and deteriorates at 48 months after completion of LIESWT. The pooled data from meta-analyses including randomized controlled trials showed an overall positive effect in terms of IIEF-EF score improvement, although the estimates are small (ranging from about 2 to 4 points of the IIEF-EF) and the heterogeneity high [44]. Additionally, the combination of LIESWT and adjunctive therapy such as oral PDE5i appeared to be more effective than a single-agent therapy [45].…”
Section: Clinical Outcomesmentioning
confidence: 95%
“…No patients reported significant penile pain or required analgesia during LIESWT session. To date, treatment-related adverse events have been reported in published clinical trials as well as systematic reviews and meta-analyses [31,32,34,[39][40][41][42]44]. Furthermore, there is no reported drop-out rate during LIESWT due to treatment-related adverse events.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…There are several national and international organizations that have published guideline recommendations surrounding LiSWT including the AUA (2018), Asia-Pacific Society for Sexual Medicine (APSSM; 2020), European Society of Sexual medicine (ESSM; 2019), and European Association of Urology (EAU; 2020) (3,(58)(59)(60). All organizations acknowledge LiSWT as a potential treatment for ED with promising early clinical studies.…”
Section: Discussionmentioning
confidence: 99%